2020
DOI: 10.3390/ijms22010093
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Flow Cytometry: A Robust Tool to Assess Physiological Parameters Related to the Fertilizing Capability of Human Sperm

Abstract: Plasma membrane (PM) hyperpolarization, increased intracellular pH (pHi), and changes in intracellular calcium concentration ([Ca2+]i) are physiological events that occur during human sperm capacitation. These parameters are potential predictors of successful outcomes for men undergoing artificial reproduction techniques (ARTs), but methods currently available for their determination pose various technical challenges and limitations. Here, we developed a novel strategy employing time-lapse flow cytometry (TLFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Firstly, the calibration plot of theoretical membrane potential and median fluorescence intensity of DiSC 3 (5) (3,3′ dipropylthiadicarbocyanine iodide) (Invitrogen, Eugene, OR, USA) was generated by time-lapse flow cytometry as detailed in Matamoros-Volante et al (2020) [ 46 ] ( Supplemental Figure S1 ). Briefly, non-capacitated boar sperms were diluted to a final concentration of 1–3 × 10 6 cells/mL in non-capacitating media (in mM: NaCl 90, KCl 4.68, glucose 2.78, CaCl 2 1.8, KH 2 PO 4 0.37, MgSO 4 0.2, sodium pyruvate 0.33, sodium lactate 21.39, HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) 23.8, pH adjusted to 7.4 with NaOH).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the calibration plot of theoretical membrane potential and median fluorescence intensity of DiSC 3 (5) (3,3′ dipropylthiadicarbocyanine iodide) (Invitrogen, Eugene, OR, USA) was generated by time-lapse flow cytometry as detailed in Matamoros-Volante et al (2020) [ 46 ] ( Supplemental Figure S1 ). Briefly, non-capacitated boar sperms were diluted to a final concentration of 1–3 × 10 6 cells/mL in non-capacitating media (in mM: NaCl 90, KCl 4.68, glucose 2.78, CaCl 2 1.8, KH 2 PO 4 0.37, MgSO 4 0.2, sodium pyruvate 0.33, sodium lactate 21.39, HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) 23.8, pH adjusted to 7.4 with NaOH).…”
Section: Methodsmentioning
confidence: 99%
“…When undergoing capacitation, sperm cells become hyperpolarized, their intracellular pH becomes more alkaline, and there is an increased response to Ca 2+ induced by progesterone in the female reproductive tract. Volante et al used Time‐Lapse Flow Cytometry measurements to measure these physiological changes in spermatozoa as they happened in real‐time and compared the results from two groups of men with either known paternity ( n = 7) or those with no paternity and no known fertility issues ( n = 6) (Matamoros‐Volante et al, 2020). They found that all of the samples in the known paternity group hyperpolarized and had an alkaline intracellular change in pH during capacitation, while only 44% of those from the no‐paternity group hyperpolarized and only 17% had an alkaline intracellular pH change.…”
Section: Capacitation Evaluation As a Predictor Of Fertility In Other...mentioning
confidence: 99%
“…Sperm membrane potential changes were measured using the membrane-potentialsensitive fluorochrome: 3,3 -dipropyl thiadicarbo cyanine iodide (DISC 3 ) (Cat#306, Invitrogen, Thermo Fisher Scientific, Waltham, MA 0251, USA). Temporal variation in membrane potential with different treatments was detected using a time-lapse flow cytometry setup, as explained in Matamoros-Volante et al 2021 [63]. To validate this technique, we followed Matamoros-Volante's protocol to generate standard curves using valinomycin and different potassium concentrations for theoretical membrane potential and fit the linear equation (Supplementary Figure S3).…”
Section: Membrane Potential Measurementmentioning
confidence: 99%
“…The normalized median DiSC 3 values were considered for comparisons between the different treatment groups. The equation (F x − F 0 )/F 0 was used for the data normalization of a sample, where F x and F 0 denote the fluorescence at a given point and fluorescence at a stable basal level, respectively [63].…”
Section: Membrane Potential Measurementmentioning
confidence: 99%